2018
DOI: 10.1038/s41598-017-18590-6
|View full text |Cite
|
Sign up to set email alerts
|

Shape dependent physical mutilation and lethal effects of silver nanoparticles on bacteria

Abstract: In this report, spherical silver nanoparticle (AgNP-sp) and rod-shaped silver nanoparticle (AgNR) were prepared by chemical reduction method and their antibacterial activity against various Gram-positive and Gram-negative bacteria had been evaluated for their efficiency. Minimal inhibitory concentration (MIC) tests were conducted to study the antibacterial properties, and substantiated with killing kinetics of silver nanoparticles (AgNPs). The study revealed that both AgNP-sp and AgNRs are good antibacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 34 publications
4
81
0
Order By: Relevance
“…It has been reported that the antibacterial or bactericidal properties of silver nanoparticles are shape and size‐dependent and smaller particles (<30 nm) were more effective against K. pneumoniae and S. aureus , while spherical particles are more active than rod shape . In our study, the nanoparticles Ag‐NP‐AE is spherical with an average diameter of 27 nm, that may attribute to the release of silver ions responsible for bactericidal activity of Ag‐NP‐AE at extremely low concentrations (0.5–0.84 μM or 0.085–0.143 μg); while AE of A. lebbeck bark showed anti‐bacterial activity at 128–1024 μg/mL, i. e., at much higher concentrations against all the bacterial isolates tested.…”
Section: Discusssionmentioning
confidence: 48%
See 3 more Smart Citations
“…It has been reported that the antibacterial or bactericidal properties of silver nanoparticles are shape and size‐dependent and smaller particles (<30 nm) were more effective against K. pneumoniae and S. aureus , while spherical particles are more active than rod shape . In our study, the nanoparticles Ag‐NP‐AE is spherical with an average diameter of 27 nm, that may attribute to the release of silver ions responsible for bactericidal activity of Ag‐NP‐AE at extremely low concentrations (0.5–0.84 μM or 0.085–0.143 μg); while AE of A. lebbeck bark showed anti‐bacterial activity at 128–1024 μg/mL, i. e., at much higher concentrations against all the bacterial isolates tested.…”
Section: Discusssionmentioning
confidence: 48%
“…To cater the need scientists are looking into a metal nano‐particle based drugs, as nano‐sized molecules (<100 nm) have larger surface area than their volume, and thus able to penetrate the microbial cells faster to kill at nano‐dose . Another advantage is its ability to kill bacteria on contact, by bypassing the bacterial resistant mechanisms i. e., enzymatic inactivation, decreased cell permeability, altered target site, increased efflux due to overexpression of efflux pumps, and mutation of existing genes or acquiring new genes . In this study, we have reported the biosynthesis of silver nanoparticles using AgNO 3 and aqueous extract of bark of a traditionally used well known ethnomedicinal plant as reducing and stabilizing agents, because metallic nanoparticles from medicinal plant extracts posse's biocompatibility and antimicrobial activity.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…AgNPs are generally obtained from colloidal dispersions, and depending on the method used during synthesis could display a variety of morphologies, including nanocubes, nanoprisms, nanospheres, triangular nanoplates and rod‐like shapes (Huang, Zhai, Dong, & Wang, ; Sarkar, Kapoor, & Mukherjee, ). A study comparing the antibacterial activity of spherical and triangular Ag nanoprisms against Escherichia coli showed that they exerted greater bacterial toxicity due to their sharp edges with triangular shape (Acharya et al, ). Similarly, truncated triangular AgNPs display stronger biocidal action than that observed by spherical and rod‐shaped NPs (Pal, Tak, & Song, ).…”
Section: Structure‐activity Relationships Of Silver Nanoparticles Witmentioning
confidence: 99%